93.7k views
4 votes
3 (2x-1 ) +7 = - 44 ( solve for x)

1 Answer

0 votes

Answer:

x = - 8

Explanation:

To solve for x, isolate it by "moving" everything else over to the other side. This is done in reverse BEDMAS order using the reverse operations of number you want to move.

3 (2x-1 ) +7 = - 44 Simplify first using distributive property over the brackets

6x - 3 + 7 = - 44 Combine like terms, terms that have the same variables

6x + 4 = - 44

6x + 4 - 4 = - 44 - 4 Subtract 4 from both sides to cancel it out on the left side

6x = - 48

6x/6 = - 48/6 Divide by sides by 6 to cancel out the 6 from 6x

x = - 8 Final answer

User Eugene Burmako
by
5.1k points